Cover Feature: Singlet Fission in Enantiomerically Pure Pentacene Dimers (ChemPhotoChem 10/2020). Issue 10 (13th October 2020) - Papadopoulos, Ilias; Gao, Yueze; Hetzer, Constantin; Tykwinski, Rik R.; Guldi, Dirk M.
Abstract : The Cover Feature highlights the mirror‐image relationship between two enantiomeric dimers used to explore singlet fission (SF) in the presence of a heavy atom. Spectroscopic techniques outline SF through a virtual CT intermediate that is independent of chirality (cover art by Annie Tykwinski; background photo courtesy of James Wheeler on Unsplash). More information can be found in the Article by R. R. Tykwinski, D. M. Guldi, and co‐workers .